2020
DOI: 10.1073/pnas.2000698117
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of relaxation and excess entropy in plastically deformed amorphous solids

Abstract: When stressed sufficiently, solid materials yield and deform plastically via reorganization of microscopic constituents. Indeed, it is possible to alter the microstructure of materials by judicious application of stress, an empirical process utilized in practice to enhance the mechanical properties of metals. Understanding the interdependence of plastic flow and microscopic structure in these nonequilibrium states, however, remains a major challenge. Here, we experimentally investigate this relationship, betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…Intuitively, the condition b = c should correspond to mechanical equilibrium, with no imposed shear stress in either direction. However, Galloway et al (39,40) found that an elliptical signature could be detected even at equilibrium and that it survived further shear deformations below the yielding transition, so that its disappearance was a proxy for yielding. They identified it as the memory of an earlier large plastic deformation, consistent with scattering results from bulk metallic glasses that were previously deformed (4,41,42).…”
Section: Effect Of Annealing On Microscopic Structurementioning
confidence: 99%
“…Intuitively, the condition b = c should correspond to mechanical equilibrium, with no imposed shear stress in either direction. However, Galloway et al (39,40) found that an elliptical signature could be detected even at equilibrium and that it survived further shear deformations below the yielding transition, so that its disappearance was a proxy for yielding. They identified it as the memory of an earlier large plastic deformation, consistent with scattering results from bulk metallic glasses that were previously deformed (4,41,42).…”
Section: Effect Of Annealing On Microscopic Structurementioning
confidence: 99%
“…Intuitively, the condition b = c should correspond to mechanical equilibrium, with no imposed shear stress in either direction. However Galloway et al (39,40) found that an elliptical signature could be detected even at equilibrium, and that it survived further shear deformations below the yielding transition. They identified it as the memory of an earlier large plastic deformation-consistent with scattering results from bulk metallic glasses that were previously deformed (5,41,42).…”
Section: Effect Of Annealing On Microscopic Structurementioning
confidence: 99%
“…Even though S 2 has been introduced long ago 54,55 , it is a useful concept that continues to be widely used 17,[56][57][58] . As a matter of fact, recently, scaling relations have been reported between S 2 and diffusivity in glassy systems 59 and relaxation rates in cyclic sheared systems 60 . In order to look at this quantity on a single-particle level, the two-body entropy of particle i can be defined as:…”
Section: Local Entropymentioning
confidence: 99%